Impact of C57BL/6J and SV-129 Mouse Strain Differences on Ischemia-Induced Postnatal Angiogenesis and the Associated Leukocyte Infiltration in a Murine Hindlimb Model of Ischemia - Matthias Kübler (MDPI AG, 2021)
Strain-related differences in arteriogenesis in inbred mouse strains have already been studied excessively. However, these analyses missed evaluating the mouse strain-related differences in ischemia-induced angiogenic capacities. With the present study, we wanted to shed light on the different angiogenic potentials and the associated leukocyte infiltration of C57BL/6J and SV-129 mice to facilitate the comparison of angiogenesis-related analyses between these strains. For the induction of angiogenesis, we ligated the femoral artery in 8–12-week-old male C57BL/6J and SV-129 mice and performed (immuno-) histological analyses on the ischemic gastrocnemius muscles collected 24 h or 7 days after ligation. As evidenced by hematoxylin and eosin staining, C57BL/6J mice showed reduced tissue damage but displayed an increased capillary-to-muscle fiber ratio and an elevated number of proliferating capillaries (CD31+/BrdU+ cells) compared to SV-129 mice, thus showing improved angiogenesis. Regarding the associated leukocyte infiltration, we found increased numbers of neutrophils (MPO+ cells), NETs (MPO+/CitH3+/DAPI+), and macrophages (CD68+ cells) in SV-129 mice, whereas macrophage polarization (MRC1- vs. MRC1+) and total leukocyte infiltration (CD45+ cells) did not differ between the mouse strains. In summary, we show increased ischemia-induced angiogenic capacities in C57BL/6J mice compared to SV-129 mice, with the latter showing aggravated tissue damage, inflammation, and impaired angiogenesis.